2018
DOI: 10.1161/hypertensionaha.117.10094
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-221/222 Family Counteracts Myocardial Fibrosis in Pressure Overload–Induced Heart Failure

Abstract: Pressure overload causes cardiac fibroblast activation and transdifferentiation, leading to increased interstitial fibrosis formation and subsequently myocardial stiffness, diastolic and systolic dysfunction, and eventually heart failure. A better understanding of the molecular mechanisms underlying pressure overload-induced cardiac remodeling and fibrosis will have implications for heart failure treatment strategies. The microRNA (miRNA)-221/222 family, consisting of miR-221-3p and miR-222-3p, is differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
93
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(104 citation statements)
references
References 56 publications
8
93
1
2
Order By: Relevance
“…Interestingly, treatment with the anti-fibrotic drug pirfenidone led to a 2.1-fold increase in the miR-221 expression in the HF-chip tissues ( Supplemental Table 1), and an even higher increase in extracellular vesicles (32-fold). This is in line with its recently described role in counteracting myocardial fibrosis in pressure overload-induced heart failure by blunting TGF-β-induced pro-fibrotic signaling (Verjans et al, 2018) and suggests a possible new mechanism of action for the drug. It also demonstrates the potential of the human HF-chip platform to validate animal findings in a human-relevant model.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Interestingly, treatment with the anti-fibrotic drug pirfenidone led to a 2.1-fold increase in the miR-221 expression in the HF-chip tissues ( Supplemental Table 1), and an even higher increase in extracellular vesicles (32-fold). This is in line with its recently described role in counteracting myocardial fibrosis in pressure overload-induced heart failure by blunting TGF-β-induced pro-fibrotic signaling (Verjans et al, 2018) and suggests a possible new mechanism of action for the drug. It also demonstrates the potential of the human HF-chip platform to validate animal findings in a human-relevant model.…”
Section: Discussionsupporting
confidence: 82%
“…It also suggests that the loading of particular miRs into vesicles is a highly specific and regulated process. In support of this, we saw that miR-221, found to target TGF-β-mediated pro-fibrotic SMAD2 (mothers against decapentaplegic homolog 2) signaling and its downstream gene expression (Verjans et al, 2018), was not differentially expressed in control or fibrotic tissues but was significantly downregulated in secreted extracellular vesicles in fibrotic samples. Interestingly, treatment with the anti-fibrotic drug pirfenidone led to a 2.1-fold increase in the miR-221 expression in the HF-chip tissues ( Supplemental Table 1), and an even higher increase in extracellular vesicles (32-fold).…”
Section: Discussionmentioning
confidence: 69%
“…Reduced myocardial miR-221/222 expression is associated with severe cardiac fibrosis in heart failure patients [95]. miR-221 overexpression has been shown to induce cardiac hyperthropy in vitro [96] and to promote HF [147].…”
Section: Mir-221/222mentioning
confidence: 99%
“…miR-221 overexpression has been shown to induce cardiac hyperthropy in vitro [96] and to promote HF [147]. Indeed, miR-221/222 are significantly upregulated in patients with hypertrophic cardiomyopathy [95].…”
Section: Mir-221/222mentioning
confidence: 99%
“…Jeong et al indicate that miR-25 TuD (Tough Decoy) is an effective long-term suppressor of miR-25 and a promising therapeutic candidate to treat heart failure in humans [11]. According to Verjans, heart failure-associated down regulation of the miRNA-221/222 family enables fibrosis signaling in a pressure-overloaded heart in rats [12]. In our previous study, we showed in chickens that regulation of miR-200a-5p and its target gene blocks necroptosis in the heart, which revealed a novel myocardial necrosis regulation model in heart disease [13].…”
Section: Introductionmentioning
confidence: 99%